Carnosine: Effect on aging-induced increase in brain regional monoamine oxidase-A activity. (March 2015) - Banerjee, Soumyabrata; Poddar, Mrinal K.
Highlights: The brain regional MAO-A activity and their V max and K m are increased with aging. Carnosine inhibits young (4 months) rat brain regional MAO-A activity. Carnosine attenuates the aging-induced increase of MAO-A activity toward young. Effective dosages of carnosine is 1.0–2.5 μg/kg/day, i.t. for 21 consecutive days. Abstract: Aging is a natural biological process associated with several neurological disorders along with the biochemical changes in brain. Aim of the present investigation is to study the effect of carnosine (0.5–2.5 μg/kg/day, i.t. for 21 consecutive days) on aging-induced changes in brain regional (cerebral cortex, hippocampus, hypothalamus and pons-medulla) mitochondrial monoamine oxidase-A (MAO-A) activity with its kinetic parameters. The results of the present study are: (1) The brain regional mitochondrial MAO-A activity and their kinetic parameters (except in K m of pons-medulla) were significantly increased with the increase of age (4–24 months), (2) Aging-induced increase of brain regional MAO-A activity including its V max were attenuated with higher dosages of carnosine (1.0–2.5 μg/kg/day) and restored toward the activity that observed in young, though its lower dosage (0.5 μg/kg/day) were ineffective in these brain regional MAO-A activity, (3) Carnosine at higher dosage in young rats, unlike aged rats significantly inhibited all the brain regional MAO-A activity by reducing their only V max excepting cerebral cortex, where K m was also significantly enhanced. These results suggest that carnosine attenuated the aging-induced increase of brain regional MAO-A activity by attenuating its kinetic parameters and restored toward the results of MAO-A activity that observed in corresponding brain regions of young rats.